Protein C concentrate controls leukocyte recruitment during inflammation and improves survival during endotoxemia after efficient in vivo activation - Frommhold, David; Tschada, Julia; Braach, Natascha; Buschmann-Prayon, Kirsten; Dörner, Axel; Pflaum, Johanna; Metzger, Marie-Sophie; Wang, Hongjie; Koch, Lutz; Sperandio, Markus; Bierhaus, Angelika; Isermann, Berend; et al. (The American journal of pathology, 2011)
Anti-inflammatory properties of protein C (PC) concentrate are poorly studied compared to activated protein C, although PC is suggested to be safer in clinical use. We investigated how PC interferes with the leukocyte recruitment cascade during acute inflammation and its efficacy during murine endotoxemia. We found that similar to activated protein infusion, intravenous PC application reduced leukocyte recruitment in inflamed tissues in a dose- and time-dependent manner. During both tumor necrosis factor-α induced and trauma-induced inflammation of the cremaster muscle, intravital microscopy revealed that leukocyte adhesion and transmigration, but not rolling, were profoundly inhibited by 100 U/kg PC. Moreover, PC blocked leukocyte emigration into the bronchoalveolar space during lipopolysaccharide (LPS) induced acute lung injury. PC was efficiently activated in a murine endotoxemia model, which reduced leukocyte infiltration of organs and strongly improved survival (75% versus 25% of control mice). Dependent on the inflammatory model, PC provoked a significant inhibition of leukocyte recruitment as early as 1 hour after administration. PC-induced inhibition of leukocyte recruitment during acute inflammation critically involves thrombomodulin-mediated PC activation, subsequent endothelial PC receptor and protease-activated receptor-1-dependent signaling, and down-regulation of intercellular adhesion molecule 1 leading to reduced endothelial inflammatory response. We conclude that during acute inflammation and sepsis, PC is a fast acting and effective therapeutic approach to block leukocyte recruitment and improve survival.